Piezometer Time-Lag and Pore Pressure Ratio for Identification of Dam Internal Erosion - Thepjunthra, Wiphada; Mairaing, Warakorn; Jinakulwipat, Montri; Chalermpornchai, Thawatchai; Kunsuwan, Bunpoat (Civil Engineering Journal, 2025)
Earth dams on complex geology without proper foundation treatment often face the risk of seepage problems. Sufficient installation and interpretation of field instruments are essential for monitoring dam behavior. Three indicators are introduced for assessment of seepage behavior: time lag (TL), pore pressure ratio (PR), and trigger water level (HW). The normalized TL reflects the washing out and plugging of rock cracks, as well as the progression of internal erosion. The foundation of the studied dam consisted of foliated rocks that were highly fractured, with the axis of the foliations aligned almost in the upstream-downstream direction, with a possible low-stress zone on the syncline axis. The existing crack easily opened in the concave section of the syncline when the reservoir had risen to a certain elevation, resulting in increased permeability and a higher flow to the downstream area, known as “hydraulic fracturing” (HF). The piezometer TL clearly indicated a shorter response time as the operating period progressed. The study dam showed the possibility of HF in the foundation, as observed during 2003–2024. The progression of HF was also confirmed by the increase in PR levels toward downstream. This revealed that the ongoing progression of HF had occurred at sta.2+700, which agreed well with the location of the slip zone that had occurred in 1993. HWwas activated by the reservoir water level response also decreasing with time from 2003 to 2024, confirming that water infiltration through the rock crack progressed with time. These three indicators could act as good warning indices for seepage problems. This compiled knowledge could be transformed into a flowchart to identify the possible risks of hydraulic fracturing in the dam. If the three indices all showed the same trend, the potential for hydraulic fracturing and internal erosion would be very high. Doi: 10.28991/CEJ-2025-011-03-019 Full Text: PDF